NIMG-68. MRI CHANGES IN NEWLY DIAGNOSED GLIOBLASTOMA PATIENTS TREATED AS PART OF A PHASE II TRIAL WITH BAVITUXIMAB, RADIATION, AND TEMOZOLOMIDE. (5th November 2018) - Ly, Ina; Cardona, Jonathan; Beers, Andrew; Chang, Ken; Brown, James; Reardon, David; Arrillaga-Romany, Isabel; Dietrich, Jorg; Forst, Deborah; Lee, Eudocia; Jordan, Justin; Nayak, Lakshmi; et al.
Abstract: BACKGROUND: Glioblastoma and tumor endothelial cells express phosphatidylserine, a highly immunosuppressive membrane phospholipid. Bavituximab a chimeric monoclonal antibody binds to 2-glycoprotein 1 (2-GP1) to form a complex of 2-GP1 with phosphatidylserine, resulting in immune activation against tumor cells and anti-angiogenic effects. Phase I/II trials in other solid cancers have demonstrated response rates up to 85% when bavituximab was given with cytotoxic chemotherapy. Pre-clinical data in glioblastoma models suggested synergistic effects of phosphatidylserine blockade, radiation, and temozolomide (TMZ). METHODS: In this ongoing phase II trial (NCT03139916), adult patients with IDH-wild-type newly diagnosed glioblastoma receive 6 weeks of chemoradiation, followed by 6 cycles of adjuvant TMZ (C1-C6 aTMZ). Bavituximab (3 mg/kg) is given weekly, starting week 1 of chemoradiation, for 18 weeks with the option to continue if tolerated. Physiologic MRIs are performed pre-treatment, pre-C1, pre-C3, and pre-C5 aTMZ. Within the enhancing tumor region, we measured median tumor Ktrans (reflecting vascular permeability) and relative cerebral blood volume (rCBV). Median percent changes during treatment were compared to pre-treatment values. RESULTS: To date, 25 of 36 anticipated patients have enrolled (10 with MGMT promoter methylation). All patients underwent pre-treatment scans. 13 have evaluable pre-C1 and 8 pre-C3 aTMZ scans. On the pre-C1 MRIs, enhancing volume decreased by 39% and median tumor Ktrans and rCBV did not change significantly. On the pre-C3 MRIs, enhancing volume decreased by 11% and Ktrans and rCBV decreased by 17% and 21%, respectively. Five patients experienced radiographic disease progression after a median of 2.6 months and 1 patient died 76 days after diagnosis due to disease progression. Bavituximab was generally well tolerated. CONCLUSIONS: Combining bavituximab with radiation and temozolomide results in decreased enhancing tumor volume, permeability, and cerebral perfusion. Continued patient accrual and imaging marker evaluation are underway to investigate the correlation between bavituximab, MRI changes, and survival.